The role of ACER2 in intestinal sphingolipid metabolism and gastrointestinal cancers - Liu, Binggang; Zhou, Junfeng; Jiang, Biao; Tang, Bing; Liu, Ting; Lei, Pengcheng (Frontiers in Immunology, 2024)
Sphingolipids, particularly sphingosine-1-phosphate (S1P), are bioactive lipids involved in regulating cellular processes such as proliferation, apoptosis, inflammation, and tumor progression. Alkaline ceramidase 2 (ACER2) plays a critical role in sphingolipid metabolism by catalyzing the hydrolysis of ceramide to sphingosine, which is subsequently converted to S1P. Dysregulation of ACER2 has been implicated in various gastrointestinal cancers, including colorectal cancer, gastric cancer, and hepatocellular carcinoma. ACER2-mediated sphingolipid signaling, particularly through the SphK/S1P pathway, influences cancer development by modulating immune responses, inflammation, and the balance between cell survival and death. This review examines the physiological functions of ACER2, and its role in sphingolipid metabolism, and its contribution to the pathogenesis of gastrointestinal cancers. Understanding the mechanisms by which ACER2 regulates tumor progression and immune modulation may open new avenues for targeted therapies in gastrointestinal malignancies.